Preliminary Study on Long Fixation in Histological Preparations of Internal Organs of Sprague Dawley Rats - Galang Prahanarendra; Devy Ariany; Nurlaely Mida Rachmawati; Luluk Hermawati; Ghea Farmaning Thias Putri (Stem Cell and Cancer Research (SCCR), 2025)
Histotechnology is a series of processes ranging from tissue handling to the preparation of slides that can be observed under a microscope. One crucial stage in this process is fixation, which serves to preserve the structure and morphology of the tissue as close as possible to its original physiological state. However, prolonged fixation duration may lead to tissue hardening, dissolution, and structural damage. This study aims to obtain supporting data for the development of a standard operating procedure (SOP) in histotechnology that can be applied in the animal house and histology laboratories of the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta. The results showed that fixation for three weeks caused morphological damage to the kidney, liver, and pancreas of Sprague Dawley rats. The findings included tissue perforation in all three organs, endothelial nuclear damage in the kidney, central vein wall damage in the liver, and cellular disintegration in the pancreatic islets of Langerhans. Based on these findings, it can be concluded that a fixation duration of three weeks does not produce optimal histological images and therefore cannot be used as a reference for establishing a standard histotechnology SOP in the laboratory of the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta.